Pengaruh Video Berseri Terintegrasi Hikayat Aceh terhadap Pemahaman Siswa dalam Memilah Sampah - Mahlianurrahman Mahlianurrahman; Cut Kumala Sari; Muhammad Febri Rafli (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Teachers have not handled the learning of waste sorting material systematically due to the inappropriate use of learning media, so that students' understanding of waste sorting is low. This study aims to analyze the effect of integrated video series of Acehnese tales on students' understanding of waste sorting. The type of research used is a quasi-experimental with a pretest-posttest non-equivalent control group design. The study population was 154 students and the research sample was 43 students selected by random sampling. The instrument used was a test. Data analysis used independent samples t-testt. The results showed that the average score of understanding of waste sorting in the experimental class was 88.69 while the control class was 72.27 and there was a difference between the experimental group and the control group, with a significance value of 0.000 <0.005. The results of this study indicate that there is a significant difference in students' understanding of waste sorting between the experimental group and the control group. It can be concluded that the integrated video series of Acehnese tales has an effect on understanding of waste sorting.Guru belum menangani pembelajaran materi pemilahan sampah secara sistematis disebabkan ketidaktepatan penggunaan media pembelajaran, sehingga pemahaman siswa mengenai pemilahan sampah rendah. Penelitian ini bertujuan untuk mengetahui pengaruh video berseri terintegrasi hikayat Aceh terhadap pemahaman siswa dalam memilah sampah. Jenis penelitian yang digunakan adalah quasi eksperimen dengan desain pretest-posttest non-equivalent control group. Populasi penelitian berjumlah 154 siswa dan sampel penelitian berjumlah 23 orang siswa yang dipilih secara random sampling. Instrumen yang digunakan adalah tes. Analisis data menggunakan uji independent sample t-test. Hasil penelitian menunjukkan bahwa rata-rata skor pemahaman memilah sampah pada kelas eksperimen sebesar 88,69 sedangkan kelas kontrol sebesar 72,27 serta terdapat perbedaan antara kelompok eksperimen dan kelompok kontrol, dengan nilai signifikansi 0,000 < 0,005. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan signifikan pemahaman siswa dalam memilah sampah antara kelompok eksperimen dan kelompok kontrol. Dapat disimpulkan bahwa video berseri terintegrasi hikayat Aceh memiliki pengaruh terhadap pemahaman memilah sampah.